2016
DOI: 10.1016/j.jsps.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution rate improvement of telmisartan through modified MCC pellets using 32 full factorial design

Abstract: Microcrystalline cellulose (MCC) is the most widely used excipient for the production of pellets but it retards the release of poorly water soluble drugs. The present investigation reports incorporation of camphor, cross carmellose sodium (CCS) and spray dried lactose (SDL) into MCC pellets to enhance the dissolution rate of telmisartan. A full factorial design (3) was used in the study. Concentration of camphor and CCS was selected as independent variables whereas percentage porosity and percentage drug relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Specifically, sodium hydroxide, (NaOH, a strong alkalizer), povidone (K25, widely used as binder and tablet disintegrant), and meglumine (a solubilizing agent) which could have resulted in higher solubility, therefore, enhanced the dissolution profile of the commercial formulation compared to the F8 tablets. Addition of a few excipients such as strong alkalizer (NaOH), super disintegrant, or solubilizing agents may increase the release kinetics of TEL from the F8 tablets as reported in the prior literature [ 30 , 42 ]. However, the study aims to address the stability issue observed with the marketed formulation (MICARDIS ® ) and meanwhile, enhance the solubility and bioavailability of poorly soluble TEL.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, sodium hydroxide, (NaOH, a strong alkalizer), povidone (K25, widely used as binder and tablet disintegrant), and meglumine (a solubilizing agent) which could have resulted in higher solubility, therefore, enhanced the dissolution profile of the commercial formulation compared to the F8 tablets. Addition of a few excipients such as strong alkalizer (NaOH), super disintegrant, or solubilizing agents may increase the release kinetics of TEL from the F8 tablets as reported in the prior literature [ 30 , 42 ]. However, the study aims to address the stability issue observed with the marketed formulation (MICARDIS ® ) and meanwhile, enhance the solubility and bioavailability of poorly soluble TEL.…”
Section: Resultsmentioning
confidence: 99%
“…4, Y = b 0 +b 1 X 1 +b2X 2 +b 12 X 1 X 2 +b 11 X 1 2 +b 22 X 2 2 , where, Y is the measured response associated with each factor level combination; b 0 is an intercept; b 1 to b 22 are regression coefficients computed from the observed experimental values of Y, and X 1 and X 2 are the coded levels of independent variables. The terms X 1 X 2 and Xi 2 (i = 1, and 2) represent the interaction and quadratic terms, respectively [21] . The dependent and independent variables selected are shown in Table 2 along with their low, medium and high levels.…”
Section: Experimental Designmentioning
confidence: 99%
“…Obtention of immediate-release systems, with a focus on masking drug flavor (Hamedelniel, Bajdik, Pintye-Hódi, 2010;Issa et al, 2012b;Patel, Patel, Patel, 2010);  Controlled-release (Abbaspour, Sadeghi, Garekani, 2008;Bialleck, Rein, 2011;Cantor, Hoag, Augsburger, 2009a;Cantor, Hoag, Augsburger, 2009b;Franc et al, 2015;Ghanam, Kleinebudde, 2011;Ghosh, Chakraborty, 2013;Han et al, 2013;Heckötter et al, 2011;Hung et al, 2015;Ríos, Ghaly, 2015;Roblegg et al, 2011;Szkutnik-Fiedler et al, 2014;Wang et al, 2015;Xu, Liew, Heng, 2015;You et al, 2014);  Improvement in dissolution of poorly soluble drugs (Abdalla, Mader, 2007;Abdalla, Klein, Mader, 2008;Chopra, Venkatesan, Betageri, 2013;Ibrahim, El-Badry, 2014;Lu et al, 2009;Patel et al, 2016);  Gastro-retentive systems/ floating systems (Amrutkar, Chaudhari, Patil, 2012;Li et al, 2014;Pagariya, Patil, 2013;Qi et al, 2015;Zhang et al, 2012);  Enteric release/gastro-resistant systems (Andreo-Filho et al, 2009;Ghanam, Kleinebudde, 2011;Pund et al, 2010);  Improvement of plant extract or active ingredient stability (Araújo-Junior et al, 2013;Beringhs et al, 2012;Bu...…”
Section: Multiparticulate Dosage Forms and Drug Delivery Systemsmentioning
confidence: 99%